Battery diaphragm, biomass polyester adhesive and preparation method thereof

Through the preparation method of biomass polyester adhesives, the problems of poor wetting performance and stability of traditional adhesives in battery separators are solved, and the efficient wetting and stability of battery separators are achieved, ensuring the safety and performance of battery structure.

CN119133770AActive Publication Date: 2024-12-13SHANGHAI ENJIE NEW MATERIALS RESEARCH CO LTD +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411274565.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-11
Publication Date
2024-12-13
Estimated Expiration
2044-09-11

AI Technical Summary

Technical Problem

Traditional adhesives have problems caused by poor wetting performance, agglomeration and environmental temperature changes in battery separators, which affect the stability and safety of the battery structure.

Method used

By using the preparation method of biomass polyester adhesive, the surface contact angle is less than 30 degrees and the peel strength is achieved by blending the enoic acid monomer with polyether monomer and enol monomer and esterification reaction with organic acid. Adhesive layer above 70N/M is used for battery separators.

Benefits of technology

It improves the wetting performance and structural stability of the battery separator, enhances the biodegradability and environmental protection of the adhesive, reduces production costs, and significantly improves the performance and safety of the battery separator.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119133770A_ABST
    Figure CN119133770A_ABST
Patent Text Reader

Abstract

The invention discloses a battery diaphragm, which comprises a base film and an adhesive layer coated on the base film, the adhesive layer comprises a biomass polyester adhesive, the surface contact angle of the adhesive layer is less than 30 degrees, and the peel strength of the adhesive layer is more than 70N / M. The preparation method of the biomass polyester adhesive comprises the following steps: blending an olefine acid monomer and a polyether monomer for a first esterification reaction, then blending a first esterification product and an enol monomer for a polymerization reaction, and blending a polymerization product and an organic acid for a second esterification reaction to obtain the biomass polyester adhesive, the polyether has a plurality of polar groups, so that the biomass polyester adhesive has excellent wettability, enol and organic acid have excellent biodegradability, and environmental pollution and health hazards can be avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of adhesives, and in particular to a polymeric adhesive based on biomass polyether, a preparation method thereof, and application in battery separators. Background Art

[0002] Adhesives are widely used as important materials in various industrial fields. In the field of battery manufacturing, Adhesives are used to ensure a strong connection between battery components. However, there are some problems with traditional adhesives during use. Due to their large molecular weight and strong intermolecular forces, they have poor wetting properties and are prone to agglomeration. This also prevents the adhesive from being evenly applied to the battery separator, indirectly resulting in poor adhesion between battery components and affecting separator performance.

[0003] Traditional adhesives, such as epoxy resin, polyurethane or acrylate adhesives, When the ambient temperature changes or under light, volatile gases will be generated and react with the air to form an explosive mixture; or self-polymerization reaction will be triggered, causing the adhesive to fail, destroying the stability of the battery structure, and indirectly affecting the efficiency and stability of the battery. Summary of the invention

[0004] Based on the limitations of the above technical means, the main purpose of the present invention is to improve the wettability and stability of traditional adhesives to improve the performance of battery separators and ensure the stability and safety of battery structures; Accordingly, one aspect of the present invention is to provide a battery separator, comprising a base film and an adhesive layer coated thereon, wherein the adhesive layer comprises a biomass polyester adhesive, and the surface contact angle of the adhesive layer is Below 30 degrees, the peel strength of the adhesive layer is above 70 N / M.

[0005] Another aspect of the present invention is to provide a method for preparing a biomass polyester adhesive. The following steps are involved: (A) blending an olefinic acid monomer with a polyether monomer to obtain a first esterification reactant, and performing a first esterification reaction to obtain a first esterification product comprising olefinic acid-polyether ester monomers; (B) blending the first esterification product with an ene alcohol monomer to obtain a polymerization reactant, and performing a polymerization reaction to obtain a polymerization product comprising an ene acid-ene alcohol-polyether ester copolymer; and (C) blending the polymerization product with an organic acid to obtain a second esterification reactant, and performing a second esterification reaction to obtain a biomass polyester adhesive.

[0006] In the preparation method as described above, the olefinic acid monomer includes acrylic acid, methacrylic acid, crotonic acid, isocrotonic acid, 2-butyl crotonic acid, cinnamic acid, maleic acid, maleic anhydride, monoalkyl maleic acid, fumaric acid, monoalkyl fumaric acid, itaconic acid, itaconic anhydride, 2-ethylacrylic acid, cis-2-pentenoic acid, trans-2-pentenoic acid, angelic acid, tiglic acid, 3,3-dimethylacrylic acid, 3-propylacrylic acid, trans-2-methyl-3-ethylacrylic acid, cis-2-methyl-3-ethylacrylic acid, 3-isopropylacrylic acid, trans-3-methyl-3-ethylacrylic acid, cis-3-methyl-3-ethylacrylic acid, 2-isopropylacrylic acid, trimethylacrylic acid, 2-methyl-3,3-diethylacrylic acid, 3-butylacrylic acid, 2-butylacrylic acid, 2-pentylacrylic acid, 2-methyl-2-hexenoic acid, trans- 3-methyl-2-hexenoic acid, 3-methyl-3-propylacrylic acid, 2-ethyl-3-propylacrylic acid, 2,3-diethylacrylic acid, 3,3-diethylacrylic acid, 3-methyl-3-hexylacrylic acid, 3-methyl-3-tert-butylacrylic acid, 2-methyl-3-pentylacrylic acid, 3-methyl-3-pentylacrylic acid, 4-methyl-2-hexenoic acid, 4-ethyl-2-hexenoic acid, 3-methyl-2-ethyl-2-hexenoic acid, 3-tert-butylacrylic acid, 2,3-dimethyl-3-ethylacrylic acid, 3,3-dimethyl-2-ethylacrylic acid, 3-methyl-3-isopropylacrylic acid, 2-methyl-3-isopropylacrylic acid, trans-2-octenoic acid, cis-2-octenoic acid, trans-2-decenoic acid, α-acetoxyacrylic acid, β-trans-aryloxyacrylic acid or α-chloro-β-E-methoxyacrylic acid.

[0007] In the preparation method described above, the polyether monomer includes polyethylene glycol monomethyl ether, polypropylene glycol monomethyl ether, pentaethylene glycol monomethyl ether, or nonaethylene glycol monomethyl ether.

[0008] In the preparation method described above, the enol monomer includes rose alcohol, nerol, citronellol, geraniol, linalool, farnesol, α-terpineol, anise alcohol or limonol.

[0009] In the preparation method as described above, the organic acid includes dimethylolpropionic acid, dimethylolbutyric acid, dimethylolhexanoic acid, glycolic acid, malic acid, citric acid, tartaric acid, succinic acid, salicylic acid, lactic acid, citraconic acid, mesaconic acid or itaconic acid.

[0010] In the preparation method as described above, the first esterification reactant includes a first catalyst, and the first catalyst is selected from Keggin heteropoly acid, Dawson heteropoly acid, Anderson heteropoly acid or Silverton heteropoly acid.

[0011] In the preparation method as described above, the first catalyst comprises a keggin-type heteropoly acid, and the keggin-type heteropoly acid is selected from phosphotungstic acid, silicotungstic acid, phosphomolybdic acid or molybdovanadic acid.

[0012] In the preparation method described above, the molar ratio of the olefinic monomer, the polyether monomer and the first catalyst is 1:(1 to 2):(0.0004 to 0.0006).

[0013] In the preparation method as described above, the polymer reactant (B) includes a free radical initiator, and the free radical initiator is selected from peroxide free radical initiators and / or azo free radical initiators.

[0014] In the preparation method as described above, the peroxide free radical initiator includes dibenzoyl peroxide, diisopropyl peroxide, di-tert-butyl peroxide, lauroyl peroxide, dodecyl peroxide, tert-butyl perbenzoate, diisopropyl peroxydicarbonate, tert-butyl peroxy(2-ethylhexanoate) or dicyclohexyl peroxydicarbonate; the azo free radical initiator includes azobisisobutyronitrile, azobisisoheptanenitrile, azobis(2-methylpropionitrile), azobis(2-methylvaleronitrile), azobiscyclohexanecarbonitrile or azobiscyclopentanecarbonitrile.

[0015] In the preparation method described above, the molar ratio of the olefinic acid-polyether ester monomer, the olefinic alcohol monomer and the free radical initiator is 1:(0.1 to 0.3):(0.02 to 0.04).

[0016] In the preparation method as described above, the second esterification reactant includes a second catalyst, and the second catalyst is selected from Keggin heteropoly acid, Dawson heteropoly acid, Anderson heteropoly acid or Silverton heteropoly acid.

[0017] In the preparation method as described above, the second catalyst comprises a keggin-type heteropoly acid, and the keggin-type heteropoly acid is selected from phosphotungstic acid, silicotungstic acid, phosphomolybdic acid or molybdovanadic acid.

[0018] In the method described above, the molar ratio of the olefinic acid-olefin alcohol-polyether ester copolymer, the organic acid and the second catalyst is 1:(0.1 to 0.2):(0.0015 to 0.0020).

[0019] Another aspect of the present invention is to provide a biomass polyester adhesive, which is prepared by the preparation method as described above.

[0020] Compared with the prior art, the present invention has the following advantages:

[0021] The present invention adopts abundant biodegradable materials as raw materials to synthesize biomass polyester adhesives with excellent performance. Due to its strong biodegradability, it can avoid environmental pollution and health hazards, broaden the raw material sources for synthesizing biomass polyester adhesives, and reduce production costs.

[0022] The present invention also improves the comprehensive performance of the biomass polyester adhesive by regulating the raw materials and the proportion. When it is applied as an adhesive layer on a battery separator, the surface contact angle can be reduced to below 30 degrees. The peel strength is increased to over 70N / M, which enhances the membrane's wettability and structural stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The block flow chart is used to illustrate the preparation method of the biomass polyester adhesive in the first embodiment. Specific process of preparation method;

[0024] Figures 2 to 4 A series of block flow charts are used to illustrate the preparation of biomass polyester adhesives. Sub-steps of steps (A), (B) and (C) in the preparation method;

[0025] Figure 5 The infrared image of the biomass polyester adhesive prepared in Example 1; and

[0026] Figure 6 The chemical reaction flow chart is used to illustrate the chemical structure changes of the monomers and copolymers involved in steps (1) to (3) in Example 1. DETAILED DESCRIPTION

[0027] The following is a description of the specific implementation of the present invention by means of several embodiments with accompanying drawings. Figure 1 The first embodiment of the present invention provides a method for preparing a biomass polyester adhesive, comprising the following steps: (A) blending an olefinic acid monomer with a polyether monomer to obtain a first esterification reactant, and performing a first esterification reaction to obtain a first esterification product comprising olefinic acid-polyether ester monomers; (B) blending the first esterification product with an ene alcohol monomer to obtain a polymerization reactant, and performing a polymerization reaction to obtain a polymerization product comprising an ene acid-ene alcohol-polyether ester copolymer; and (C) blending the polymerization product with an organic acid to obtain a second esterification reactant, and performing a second esterification reaction to obtain a biomass polyester adhesive.

[0028] In many embodiments, the olefinic monomers include acrylic acid, methacrylic acid, crotonic acid, isocrotonic acid, 2-butyl crotonic acid, cinnamic acid, maleic acid, maleic anhydride, monoalkyl maleic acid, fumaric acid, monoalkyl fumaric acid, itaconic acid, itaconic anhydride, 2-ethylacrylic acid, cis-2-pentenoic acid, trans-2-pentenoic acid, angelic acid, tiglic acid, 3,3-dimethylacrylic acid, 3-propylacrylic acid, trans-2-methyl-3-ethylacrylic acid, cis-2-methyl-3-ethylacrylic acid, 3-isopropylacrylic acid, trans-3-methyl-3-ethylacrylic acid, cis-3-methyl-3-ethylacrylic acid, 2-isopropylacrylic acid, trimethylacrylic acid, 2-methyl-3,3-diethylacrylic acid, 3-butylacrylic acid, 2-butylacrylic acid, 2-pentylacrylic acid, 2-methyl-2-hexenoic acid, trans-3-methyl-2-hexenoic acid, 3-methyl-3-propylacrylic acid, 2-ethyl-3-propylacrylic acid, 2,3-diethylacrylic acid, 3,3-diethylacrylic acid, 3-methyl-3-hexylacrylic acid, 3-methyl-3-tert-butylacrylic acid, 2-methyl-3-pentylacrylic acid, 3-methyl-3-pentylacrylic acid , 4-methyl-2-hexenoic acid, 4-ethyl-2-hexenoic acid, 3-methyl-2-ethyl-2-hexenoic acid, 3-tert-butyl acrylic acid, 2,3-dimethyl-3-ethyl acrylic acid, 3,3-dimethyl-2-ethyl acrylic acid, 3-methyl-3-isopropyl acrylic acid, 2-methyl-3-isopropyl acrylic acid, trans-2-octenoic acid, cis-2-octenoic acid, trans-2-decenoic acid, α-acetoxy acrylic acid, β-trans-aryloxy acrylic acid or α-chloro-β-E-methoxy acrylic acid.

[0029] Preferably, the olefinic acid monomers include methacrylic acid, 3,3-dimethylacrylic acid, 3-propylacrylic acid, trans-2-methyl-3-ethylacrylic acid, cis-2-methyl-3-ethylacrylic acid, 3-isopropylacrylic acid, trans-3-methyl-3-ethylacrylic acid, cis-3-methyl-3-ethylacrylic acid, 2-isopropylacrylic acid, trimethylacrylic acid, 2-methyl-3,3-diethylacrylic acid, 3-butylacrylic acid, 2-butylacrylic acid, 2-pentylacrylic acid, 3-methyl-3-propylacrylic acid, acid, 2,3-diethylacrylic acid, 3,3-diethylacrylic acid, 3-methyl-3-hexylacrylic acid, 3-methyl-3-tert-butylacrylic acid, 2-methyl-3-pentylacrylic acid, 3-methyl-3-pentylacrylic acid, 3-tert-butylacrylic acid, 2,3-dimethyl-3-ethylacrylic acid, 3,3-dimethyl-2-ethylacrylic acid, 3-methyl-3-isopropylacrylic acid, 2-methyl-3-isopropylacrylic acid, α-acetoxyacrylic acid, β-trans-aryloxyacrylic acid or α-chloro-β-E-methoxyacrylic acid.

[0030] More preferably, the ethylenic monomer comprises methacrylic acid.

[0031] In many embodiments, the average molecular weight of the polyether monomer is preferably 350 to 1000, more preferably 550, 750 or 1000; in a specific example, the polyether monomer includes polyethylene glycol monomethyl ether (CAS: 9004-74-4), polypropylene glycol monomethyl ether (CAS: 37286-64-9), pentaethylene glycol monomethyl ether (CAS: 23778-52-1), or nonaethylene glycol monomethyl ether (CAS: 6048-68-6), preferably polyethylene glycol monomethyl ether.

[0032] In some embodiments, the enol monomer includes rose alcohol (CAS: 10339-55-6), nerol (CAS: 106-25-2), citronellol (CAS: 106-22-9), geraniol (CAS: 106-24-1), linalool (CAS: 78-70-6), farnesol (CAS: 4602-84-0), α-terpineol (CAS: 98-55-5) or anise alcohol (CAS: 105-13-5), preferably rose alcohol.

[0033] In some embodiments, the organic acid includes dimethylolpropionic acid (CAS: 4767-03-7), dimethylolbutanoic acid (CAS: 10097-02-6), dimethylolhexanoic acid, glycolic acid (CAS: 79-14-1), malic acid (CAS: 6915-15-7), citric acid (CAS: 77-92-9), tartaric acid (CAS: 526-83-0), succinic acid (CAS: 110-15-6), salicylic acid (CAS: 69-72-7), lactic acid (CAS: 50-21-5), citraconic acid (CAS: 498-23-7), mesaconic acid (CAS: 498-24-8) or itaconic acid (CAS: 97-65-4).

[0034] In the above embodiment, the first esterification reactant further includes a first catalyst, which can be a Keggin-type heteropolyacid, a Dawson-type heteropolyacid, an Anderson-type heteropolyacid or a Silverton-type heteropolyacid; preferably, the first catalyst includes a keggin-type heteropolyacid, and the keggin-type heteropolyacid is selected from phosphotungstic acid (CAS: 12067-99-1), silicotungstic acid (CAS: 12027-38-2), phosphomolybdic acid (CAS: 51429-74-4) or molybdovanadic acid; in a preferred example, the keggin-type heteropolyacid includes phosphotungstic acid, such as dodecaphosphotungstic acid.

[0035] In these embodiments, the molar ratio of the olefinic monomer, the polyether monomer, and the acid catalyst is 1:(1 to 2):(0.0004 to 0.0006), preferably 1:(1 to 1.3):(0.00050 to 0.00055).

[0036] In the above embodiment, the polymerization reactant further includes a free radical initiator, which can be a peroxide free radical initiator and / or an azo free radical initiator; specifically, the peroxide free radical initiator can be dibenzoyl peroxide, diisopropyl peroxide, di-tert-butyl peroxide, lauroyl peroxide, tert-butyl perbenzoate, diisopropyl peroxydicarbonate, tert-butyl peroxy(2-ethylhexanoate) or dicyclohexyl peroxydicarbonate; the azo free radical initiator can be azobisisobutyronitrile, azobisisoheptanenitrile, azobis(2-methylpropionitrile), azobis(2-methylvaleronitrile), azobiscyclohexanecarbonitrile or azobiscyclopentanecarbonitrile; preferably, the azo free radical initiator is azobisisobutyronitrile.

[0037] In these embodiments, the molar ratio of the olefinic acid-polyether ester monomer, the olefinic alcohol monomer and the free radical initiator is 1:(0.1 to 0.3):(0.02 to 0.04), preferably 1:(0.18 to 0.25):(0.025 to 0.035).

[0038] In the above embodiment, the second esterification reactant further includes a second catalyst, which may be the same as or different from the first catalyst, and includes a Keggin-type heteropoly acid, a Dawson-type heteropoly acid, an Anderson-type heteropoly acid or a Silverton-type heteropoly acid; in a specific example, the second catalyst includes a Keggin-type heteropoly acid, such as phosphotungstic acid, silicotungstic acid, phosphomolybdic acid or molybdovanadic acid, preferably phosphotungstic acid.

[0039] In these embodiments, the molar ratio of the olefinic acid-olefinic alcohol-polyether ester copolymer, the organic acid and the second catalyst is 1:(0.1 to 0.2):(0.0015 to 0.0020), preferably 1:(0.10 to 0.15):(0.0016 to 0.0018).

[0040] In the present embodiment, the polyether used has abundant polar groups, which makes it have excellent wetting properties. By modifying the polyether, the biomass polyester adhesive has good wetting properties, can be more wetted, improve the coating performance of the biomass polyester adhesive, make it adhere to the substrate more evenly, and improve the quality and performance of the back-end product; in addition, the polyether also has good thermal stability, so that it can maintain stable performance even in high temperature environments; on the other hand, the enol monomers and organic acids used are also compounds that are easily naturally degraded; in some embodiments, alcohols (such as rose alcohol, nerol, etc.) and acids (such as malic acid, citric acid, etc.) derived from natural plants are used, which are more natural and environmentally friendly; because these compounds have unique polar structures, they have good adhesion ability, which can further improve the adhesion and stability of the biomass polyester adhesive; accordingly, the present invention uses these biodegradable materials to modify the adhesive material, which can not only reduce costs, but also reduce environmental pollution and health hazards.

[0041] See also Figure 2 The second embodiment of the present invention provides a method for preparing a biomass polyester adhesive, and the method steps, materials, and specific parameters are substantially the same as those of the first embodiment, except that the step (A) includes the following sub-steps: (A1) dispersing the acrylate monomer in a first dispersion solvent to prepare a first precursor solution; (A2) dispersing the polyether monomer and the first catalyst to obtain a second precursor solution; (A3) heating the first precursor solution to a first esterification temperature; (A4) adding the second precursor solution dropwise to the first precursor solution to obtain the first esterification reactant; and (A5) subjecting the first esterification reactant to the first esterification reaction at the first esterification temperature for a first esterification time to obtain the first esterification product, wherein the first esterification temperature is 110°C to 130°C, and the first esterification time is 6 to 8 hours; in some preferred embodiments, the first esterification temperature is 115°C to 125°C, and more preferably 115°C to 120°C.

[0042] In many embodiments, the first dispersing solvent can be a polar solvent or a non-polar solvent, wherein the polar solvent can be ethanol (EtOH), methanol (MeOH), acetone, dimethylformamide (DMF) or tetrahydrofuran (THF), and the non-polar solvent can be pentane, hexane, heptane, cyclopentane, cyclohexane, benzene, toluene, xylene, 1,4-dimethylbenzene, , dichloromethane (DCM), methyl tertiary butyl ether (MTBE), chloroform, carbon tetrachloride, diethyl ether and dichloromethane (DCM); preferably, the first dispersing solvent is a non-polar solvent, such as toluene.

[0043] In some preferred embodiments, the first precursor solution further includes an inhibitor, which may be hydroquinone, p-methoxyphenol, p-benzoquinone, phenothiazine, β-phenylnaphthylamine, p-tert-butylcatechol, methylene blue, 4,4'-butylenebis(6-tert-butyl-3-methylphenol) and 2,2'-methylenebis(4-ethyl-6-tert-butylphenol), preferably hydroquinone.

[0044] In these embodiments, the step (A1) further comprises placing the first precursor solution in a vacuum condition and heating it to a melting temperature, wherein the melting temperature is 30°C to 50°C, preferably 30°C to 40°C.

[0045] In some embodiments, the step (A4) further comprises adding the second precursor solution dropwise to the first precursor solution within 10 to 30 minutes, wherein, taking the mole number of the olefinic acid monomer as 1, the dropping rate of the polyether monomer is 0.005 to 0.01 mol per minute, and the dropping rate of the acid catalyst is 0.000075 to 0.00010 mol per minute; preferably, the second precursor solution is added dropwise to the first precursor solution within 15 to 20 minutes, the dropping rate of the polyether monomer is 0.0055 to 0.0060 mol per minute, and the dropping rate of the acid catalyst is 0.000075 to 0.00080 mol per minute.

[0046] In many embodiments, the step (A) further includes a sub-step (A6): drying the first esterification product. Specifically, the drying includes reduced pressure distillation drying, vacuum drying or hot air drying.

[0047] In the second embodiment, the step (B) comprises the following sub-steps: (B1) dispersing the olefinic acid-polyether ester monomer and the olefinic alcohol monomer in a second dispersing solvent to prepare a third precursor solution; (B2) adding the free radical initiator dropwise to the third precursor solution to obtain the polymer reactant; and (B3) heating the polymerization reactants to a polymerization temperature, and carrying out the polymerization reaction for a polymerization time to obtain the polymerization product, wherein the polymerization temperature is 80° C. to 120° C., and the polymerization time is 8 to 12 hours; in some preferred embodiments, the polymerization temperature is 90° C. to 105° C.

[0048] In many embodiments, the second dispersing solvent may be a polar solvent or a non-polar solvent that is the same as or different from the first dispersing solvent, wherein the polar solvent may include ethanol (EtOH), methanol (MeOH), acetone, dimethylformamide (DMF) or tetrahydrofuran (THF), and the non-polar solvent may include pentane, hexane, heptane, cyclopentane, cyclohexane, benzene, toluene, xylene, 1,4-dimethylformamide ... , dichloromethane (DCM), methyl tertiary butyl ether (MTBE), chloroform, carbon tetrachloride, diethyl ether and dichloromethane (DCM); preferably, the second dispersing solvent is a non-polar solvent, such as toluene.

[0049] In some embodiments, the step (B2) further comprises dripping the free radical initiator into the third precursor solution within 30 to 90 minutes, wherein, taking the molar number of the acrylate polyether ester monomer as 1, the dripping rate of the free radical initiator is 0.00022 to 0.00133 mol per minute; preferably, the free radical initiator is dripped into the third precursor solution within 30 to 60 minutes, and the dripping rate of the free radical initiator is 0.00042 to 0.0012 mol per minute.

[0050] In many embodiments, the step (B) further includes a sub-step (B4): drying the polymer product, which can be specifically carried out by reduced pressure distillation drying, vacuum drying or hot air drying.

[0051] In the second embodiment, the step (C) comprises: (C1) blending the polymerization product, the organic acid and the second catalyst to obtain a second esterification reactant; and (C2) carrying out the second esterification reaction at a second esterification temperature for a second esterification time to obtain a biomass polyester adhesive, wherein the second esterification temperature is 130 to 160° C., and the second esterification time is 6 to 8 hours; in some preferred embodiments, the second esterification temperature is 135 to 155° C.

[0052] In many embodiments, the step (C) further includes a sub-step (C3): drying the biomass polyester adhesive, which is not limited to drying by reduced pressure distillation, vacuum drying or hot air drying.

[0053] The third embodiment of the present invention provides a biomass polyester adhesive, which is prepared by the preparation method provided in the first embodiment or the second embodiment.

[0054] The fourth embodiment of the present invention is to provide a battery separator, which includes a base film and an adhesive layer coated thereon, wherein the adhesive layer contains a biomass polyester adhesive, the surface contact angle of the adhesive layer is less than 30 degrees, and the peel strength of the adhesive layer is greater than 70N / M.

[0055] In the fourth embodiment, the biomass polyester adhesive comprises the biomass polyester adhesive provided in the third embodiment.

[0056] In many embodiments, the surface contact angle of the adhesive layer is 20 to 30 degrees, preferably 22 to 27 degrees, more preferably 22 to 23 degrees, 24 to 25 degrees, or 26 to 27 degrees.

[0057] In many embodiments, the peel strength of the adhesive layer is 70 to 90 N / M, preferably 80 to 90, more preferably 80 to 85 N / M or 85 to 90 N / M.

[0058] The surface contact angle of the adhesive layer in the present invention is measured according to GBT30693-2014 Measurement of the contact angle of plastic film with water, and the peel strength is measured according to GB / T 2792-2014 Test method for peel strength of adhesive tape.

[0059] Example 1

[0060] A method for preparing a biomass polyester adhesive, comprising the following specific steps:

[0061] (1) 8.6 g (0.1 mol) of methacrylic acid and 25 ml of toluene were added to a three-necked flask equipped with an electric stirrer, a temperature controller, a constant pressure dropping funnel, a reflux condenser and a nitrogen inlet tube. The reaction temperature was 30 to 40° C. to dissolve all the reactants. At the same time, the three-necked flask was purged with nitrogen for 2 to 3 minutes, and then vacuumed for about 1 to 2 minutes. This process was repeated 3 times to remove air from the reaction system. 90 g (0.12 mol) of polyether alcohol 750 and 0.15 g (0.00052 mol) of phosphotungstic acid were injected into the constant pressure dropping funnel over 20 minutes using a 50 ml disposable syringe. The temperature was raised to 115 to 120° C. and a first esterification reaction was carried out under stirring and reflux for 6 to 8 hours. After the reaction was completed, the first esterification product was washed with distilled water for 3 to 4 times until the liquid of the first esterification product was neutral. The first esterification product was distilled under reduced pressure and vacuum dried at 60° C. for 5 hours to obtain methacrylic acid polyether ester.

[0062] (2) 40.9 g (0.05 mol) of polyether methacrylate and 1.56 g (0.01 mol) of rose alcohol were placed in a three-necked flask. After nitrogen was passed through the three-necked flask for 2 to 3 minutes, the flask was evacuated for about 1 to 2 minutes, and the process was repeated three times to remove the air in the reaction system. Using a 50 ml disposable syringe, 0.25 g (0.6% of the total mass) of azobisisobutyronitrile as a free radical initiator was injected into the constant pressure dropping funnel within 1 hour. The temperature was raised to 90 to 105° C., and a polymerization reaction was carried out under stirring and reflux for 8 to 12 hours. After the reaction was completed, the obtained polymer product was washed with methanol for 3 to 4 times, and vacuum dried at 60° C. for 5 hours to obtain rose polyether methacrylate.

[0063] (3) 9.52 g (0.01 mol) of rose polyether methacrylate, 0.16 g (0.0012 mol) of malic acid and 0.05 g (0.000017 mol) of phosphotungstic acid catalyst were stirred and refluxed at 135 to 155° C. for 6 to 8 hours for esterification reaction. After the reaction, the obtained second esterification product (which contains the biomass polyester adhesive) was washed with distilled water for 3 to 4 times until the liquid of the second esterification product was neutral. The second esterification product was distilled under reduced pressure and vacuum dried at 60° C. for 5 hours to obtain the final product, i.e., the biomass polyester adhesive.

[0064] The yield of the biomass polyester adhesive was calculated to be 52%, and the surface contact angle and peel strength of the adhesive layer were then measured; specifically, 1.5% of the product was mixed with the slurry and applied to a PE base film to form an adhesive layer. The surface contact angle of the adhesive layer was finally measured to be 22.3°, which was 64.03% better than the surface contact angle of 62° of the original coating film (without the addition of this adhesive); the peel strength of the adhesive layer was 82 N / M, which was 41.3% higher than the original coating film (PE base film) of 58 N / M.

[0065] See also Figure 5 , which is an infrared image of the biomass polyester adhesive prepared in Example 1, and please refer to Figure 6 , which specifically illustrates the chemical structure changes of the monomers and copolymers thereof involved in the reactions of steps (1) to (3) in Example 1.

[0066] Example 2

[0067] The difference from Example 1 is that the addition of 0.01 mol rose alcohol 1.56 g is changed to 0.05 mol rose alcohol 0.78 g; the yield of biomass polyester adhesive is calculated to be 52%. 1.5% of the product is mixed with the slurry and applied to the PE base film. The surface contact angle of the adhesive layer is finally measured to be 22.1°, which is 64.35% better than the surface contact angle of the original coating film of 62°; the peel strength of the adhesive layer is 79N / M. PE-based film 58N / M increased by 36.2%.

[0068] Example 3

[0069] The difference from Example 1 is that 1.56 g (0.01 mol) of rose alcohol is added instead of rose alcohol 2.34 grams (0.015 mol); the yield of the biomass polyester adhesive was calculated to be 51%, 1.5% of the product was mixed with the slurry, and then applied to the PE base film. The surface contact angle of the adhesive layer was finally measured to be 24.6°, which was 72.04% better than the surface contact angle of the original coating film of 62°; the peel strength of the adhesive layer was 82N / M, which was 41.3% higher than the original coating film of 58N / M.

[0070] Example 4

[0071] The difference from Example 1 is that 0.16 g (0.0012 mol) of malic acid is added instead of 0.134 g (0.001 mol) of malic acid; the yield of the biomass polyester adhesive is calculated to be 52%, 1.5% of the product is mixed with the slurry, and then applied to the PE base film. The surface contact angle of the adhesive layer is finally measured to be 22.3°, compared with the surface contact angle of 62° of the original coating, the surface contact angle improvement rate is 60.32%; the peel strength of the adhesive layer is 80 N / M, which is 37.9% higher than the original coating 58 N / M.

[0072] Example 5

[0073] The difference from Example 1 is that 0.16 g (0.0012 mol) of malic acid is added instead of 0.147 g (0.0011 mol) of malic acid; the yield of the biomass polyester adhesive is calculated to be 52%, 1.5% of the product is mixed with the slurry, and then applied to the PE base film. The surface contact angle of the adhesive layer is finally measured to be 22.5°, compared with the surface contact angle of 62° of the original coating, the surface contact angle improvement rate is 63.74%; the peel strength of the adhesive layer is 81 N / M, which is 39.65% higher than that of the PE base film 58 N / M.

[0074] Example 6

[0075] The difference from Example 1 is that 1% of the product is mixed with the slurry and applied to the PE base film. The final measured surface contact angle of the adhesive layer is 28.3°, which is 54.32% better than the surface contact angle of 62° of the original coating. The peel strength of the adhesive layer is 75N / M, which is 29.31% higher than the original coating 58N / M.

[0076] Example 7

[0077] The difference from Example 1 is that 2% of the product is mixed with the slurry and applied to the PE base film. The final measured surface contact angle of the adhesive layer is 26.5°, compared with the surface contact angle of 62° of the original coating, the surface contact angle improvement rate is 57.25%; the peel strength of the adhesive layer is 87N / M, which is 50% higher than the original coating 58N / M.

[0078] Example 8

[0079] The difference from Example 2 is that 2% of the product is mixed with the slurry and applied to the PE base film. The final measured surface contact angle of the adhesive layer is 28.6°, compared with the surface contact angle of 62° of the original coating, the surface contact angle improvement rate is 67.5%; the peel strength of the adhesive layer is 74N / M, which is 41.3% higher than the original coating 58N / M.

[0080] Example 9

[0081] The difference from Example 2 is that after 2% was applied to the PE base film, the surface contact angle of the adhesive layer was finally measured to be 26.6°, compared with the surface contact angle of 62° of the original coating, the surface contact angle improvement rate reached 53.87%; the peel strength of the adhesive layer was 85N / M, an increase of 46.55% over the original coating 58N / M.

[0082] Comparative Example 1

[0083] (1") 0.05 mol of methacrylic acid and 0.01 mol of rose alcohol are placed in a three-necked flask. After nitrogen is passed through the three-necked flask for 2 to 3 minutes, the flask is evacuated for about 1 to 2 minutes, and the process is repeated 3 times to remove air from the reaction system. Using a 50 ml disposable syringe, 0.25 g (0.6% of the total mass) of azobisisobutyronitrile initiator is injected into a constant pressure dropping funnel within 1 hour. The temperature is raised to 90 to 105° C., and a polymerization reaction is carried out under stirring and reflux for 8 to 12 hours. After the reaction is completed, the obtained reactant is washed with methanol for 3 to 4 times and vacuum dried at 60° C. for 5 hours to obtain rose methacrylate.

[0084] (2”) 0.01 mol of rose methacrylate, 0.0012 mol of malic acid and 0.000017 mol of phosphotungstic acid catalyst were stirred and refluxed at 135 to 155° C. for 6 to 8 hours for esterification reaction. After the reaction, the obtained reactant was washed with distilled water for 3 to 4 times until the liquid was neutral. The reaction solution was distilled under reduced pressure and vacuum dried at 60° C. for 5 hours to obtain the final product. The yield of the final product was calculated to be 38%. Thereafter, the surface contact angle and peel strength were measured. Specifically, 1.5% of the product was mixed with the slurry and applied on a PE base film to form an adhesive layer. The surface contact angle of the adhesive layer was measured to be 42°; and the peel strength of the adhesive layer was 65 N / M.

[0085] Comparative Example 2

[0086] The difference from Comparative Example 1 is that 0.01 mol of rose alcohol is added instead of 0.05 mol of rose alcohol. The test results are: the yield is 41%. 1.5% of the product is mixed with the slurry and applied to the PE base film. The surface contact angle of the coating film is finally measured to be 39°; the peel strength of the adhesive layer is 67 N / M.

[0087] Comparative Example 3

[0088] The difference from comparative example 1 is that 0.001 mol malic acid is added instead of 0.0012 mol malic acid. The test results are: the yield is 34%, 1.5% of the product is mixed with the slurry, and after being applied to the PE base film, the surface contact angle of the coating film is finally measured to be 38°; the peel strength of the adhesive layer is 70 N / M. Table 1

[0089] It can be seen from the above embodiments and comparative examples that the preparation method provided by the present invention can synthesize a biomass polyester adhesive with excellent performance. By modifying the polyether ester olefinic acid monomer, rose alcohol is added as a connecting structure for monomer polymerization, so that more polar groups are added to the olefinic acid-olefin alcohol-polyether ester copolymer obtained after the reaction, and finally the olefinic acid-olefin alcohol-polyether ester copolymer is further esterified and modified with malic acid. The obtained biomass polyester adhesive has enriched polar groups on the surface, which improves the surface contact angle of the base film to below 30°, and the olefinic acid monomer copolymer provides a strong backbone, so that the peel strength can reach at least 70N / M, preferably 80N / M.

[0090] It can be expected that the application of this new adhesive can significantly improve the wettability of the base film surface and enhance the liquid retention capacity of the battery separator. In addition, since the adhesive layer improves the peeling strength of the base film, its reliability and applicability in practical applications are significantly improved.

[0091] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A battery separator, It is characterized in that The invention comprises a base film and an adhesive layer coated thereon, wherein the adhesive layer comprises a biomass polyester adhesive, the surface contact angle of the adhesive layer is less than 30 degrees, and the peeling strength of the adhesive layer is more than 70N / M.

2. A method for preparing a biomass polyester adhesive, It is characterized in that The following steps are involved: (A) blending an olefinic acid monomer and a polyether monomer to obtain a first esterification reactant, and performing a first esterification reaction to obtain a first esterification product comprising an olefinic acid-polyether ester monomer; (B) blending the first esterification product with an ene alcohol monomer to obtain a polymerization reactant, and performing a polymerization reaction to obtain a polymerization product comprising an ene acid-ene alcohol-polyether ester copolymer; and (C) blending the polymerization product with an organic acid to obtain a second esterification reactant, and performing a second esterification reaction to obtain a biomass polyester adhesive.

3. The preparation method according to claim 2, It is characterized in that The olefinic acid monomers include acrylic acid, methacrylic acid, crotonic acid, isocrotonic acid, 2-butyl crotonic acid, cinnamic acid, maleic acid, maleic anhydride, monoalkyl maleic acid, fumaric acid, monoalkyl fumaric acid, itaconic acid, itaconic anhydride, 2-ethylacrylic acid, cis-2-pentenoic acid, trans-2-pentenoic acid, angelic acid, tiglic acid, 3,3-dimethylacrylic acid, 3-propylacrylic acid, trans-2-methyl-3-ethylacrylic acid, cis-2-methyl-3-ethylacrylic acid, 3-isopropylacrylic acid, trans-3-methyl-3-ethylacrylic acid, cis-3-methyl-3-ethylacrylic acid, 2-isopropylacrylic acid, trimethylacrylic acid, 2-methyl-3,3-diethylacrylic acid, 3-butylacrylic acid, 2-butylacrylic acid, 2-pentylacrylic acid, 2-methyl-2-hexenoic acid, trans-3-methyl- 2-hexenoic acid, 3-methyl-3-propylacrylic acid, 2-ethyl-3-propylacrylic acid, 2,3-diethylacrylic acid, 3,3-diethylacrylic acid, 3-methyl-3-hexylacrylic acid, 3-methyl-3-tert-butylacrylic acid, 2-methyl-3-pentylacrylic acid, 3-methyl-3-pentylacrylic acid, 4-methyl-2-hexenoic acid, 4-ethyl-2-hexenoic acid, 3-methyl-2-ethyl-2-hexenoic acid, 3-tert-butylacrylic acid, 2,3-dimethyl-3-ethylacrylic acid, 3,3-dimethyl-2-ethylacrylic acid, 3-methyl-3-isopropylacrylic acid, 2-methyl-3-isopropylacrylic acid, trans-2-octenoic acid, cis-2-octenoic acid, trans-2-decenoic acid, α-acetoxyacrylic acid, β-trans-aryloxyacrylic acid or α-chloro-β-E-methoxyacrylic acid.

4. The preparation method according to claim 2, It is characterized in that The polyether monomer includes polyethylene glycol monomethyl ether, polypropylene glycol monomethyl ether, pentaethylene glycol monomethyl ether, or nonaethylene glycol monomethyl ether.

5. The preparation method according to claim 2, It is characterized in that The enol monomer includes rose alcohol, nerol, citronellol, geraniol, linalool, farnesol, α-terpineol, anise alcohol or limonol.

6. The preparation method according to claim 2, It is characterized in that The organic acid includes dimethylolpropionic acid, dimethylolbutyric acid, dimethylolhexanoic acid, glycolic acid, malic acid, citric acid, tartaric acid, succinic acid, salicylic acid, lactic acid, citraconic acid, mesaconic acid or itaconic acid.

7. The preparation method according to any one of claims 1 to 5, It is characterized in that The first esterification reactant includes a first catalyst, and the first catalyst is selected from Keggin heteropoly acid, Dawson heteropoly acid, Anderson heteropoly acid or Silverton heteropoly acid.

8. The preparation method according to claim 7, It is characterized in that The first catalyst comprises a keggin-type heteropoly acid, and the keggin-type heteropoly acid is selected from phosphotungstic acid, silicotungstic acid, phosphomolybdic acid or molybdovanadic acid.

9. The preparation method according to claim 7, It is characterized in that The molar ratio of the olefinic monomer, the polyether monomer and the first catalyst is 1:(1 to 2):(0.0004 to 0.0006).

10. The preparation method according to any one of claims 2 to 6, It is characterized in that The polymer reactant comprises a free radical initiator, and the free radical initiator is selected from a peroxide free radical initiator and / or an azo free radical initiator.

11. The preparation method according to claim 10, It is characterized in that The peroxide free radical initiator includes dibenzoyl peroxide, diisopropyl peroxide, di-tert-butyl peroxide, lauroyl peroxide, dodecyl peroxide, tert-butyl perbenzoate, diisopropyl peroxydicarbonate, tert-butyl peroxy(2-ethylhexanoate) or dicyclohexyl peroxydicarbonate; the azo free radical initiator includes azobisisobutyronitrile, azobisisoheptanenitrile, azobis(2-methylpropionitrile), azobis(2-methylvaleronitrile), azobiscyclohexanecarbonitrile or azobiscyclopentanecarbonitrile.

12. The preparation method according to claim 10, It is characterized in that The molar ratio of the olefinic acid-polyether ester monomer, the olefinic alcohol monomer and the free radical initiator is 1:(0.1 to 0.3):(0.02 to 0.04).

13. The preparation method according to any one of claims 2 to 6, It is characterized in that The second esterification reactant includes a second catalyst, and the second catalyst is selected from Keggin heteropoly acid, Dawson heteropoly acid, Anderson heteropoly acid or Silverton heteropoly acid.

14. The preparation method according to claim 13, It is characterized in that The second catalyst comprises a keggin type heteropoly acid, and the keggin type heteropoly acid is selected from phosphotungstic acid, silicotungstic acid, phosphomolybdic acid or molybdovanadic acid.

15. The method of claim 13, It is characterized in that The molar ratio of the olefinic acid-olefin alcohol-polyether ester copolymer, the organic acid and the second catalyst is 1:(0.1 to 0.2):(0.0015 to 0.0020).

16. A biomass polyester adhesive, It is characterized in that It is prepared by the preparation method according to any one of claims 2 to 6.

Citation Information

Patent Citations

  • Novel biomass polyester and preparation thereof

    CN101486789A

  • Separator for rechargeable battery and rechargeable lithium battery including the same

    CN107394090A

  • Adhesive as well as preparation method and application thereof

    CN112442329A

  • Diaphragm, preparation method thereof and battery

    CN116417749A

  • Biomass / polyacrylate composite binder as well as preparation method and application thereof

    CN116478640A